Measurement of the parity-violating asymmetry parameter alpha_b and the helicity amplitudes for the decay Lambda_b->J/psi+Lambda with the ATLAS detector - Onofre, A. (2014)
A measurement of the parity-violating decay asymmetry parameter, αb, and the helicity amplitudes for the decay Λb0→J/ψ(μ+μ-)Λ0(pπ-) is reported. The analysis is based on 1400 Λb0 and Λ¯b0 baryons selected in 4.6  fb-1 of proton–proton collision data with a center-of-mass energy of 7 TeV recorded by the ATLAS experiment at the LHC. By combining the Λb0 and Λ¯b0 samples under the assumption of CP conservation, the value of αb is measured to be 0.30±0.16(stat)±0.06(syst). This measurement provides a test of theoretical models based on perturbative QCD or heavy-quark effective theory.